PEMASARAN KARET (KAJIAN STRUKTUR, PERILAKU DAN PENAMPILAN PASAR) DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Setiawan, Jeny; Dewi, Novia; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Objective of this research are to analyze market structure and market conduct at Kuantan Singingi area. Survey method and sample determination of this research in accordance with purposive sampling by using criteria 1-3 ha area with rubber plants life around 10-30 years. Market seller determinated by using Snow ball Sampling method with sample 48 farmer. The result, ojol market acces at Kuantan Singingi area mostly consist of  from two acces. Farmer sell the ojol through tauke and cooperative. Market structure at tauke level has oligopsoni conduct at moderate concentration with concentration rasio below 80% that is 69,69% and market structure at factory level has oligopsoni conduct at high concentration that is 84,04% and index Herfindahl value <1. Market conduct from market integrity show uncomplete, while transmition elasticity has value around 0,865 that show inelastis because it’s <1 and that’s show oligopsoni strength and it’s caused price increment.   Key words: Market Structure, Market Conduct, oligopsoni.